Islamophobia and the media : the portrayal of Islam since 9/11 and an analysis of the Danish cartoon controversy in South Africa - Asmal, F. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2008.